Diseño del plan de marketing del Hotel María mediante la aplicación de las 7 líneas de acción, para la promoción y comercialización de los servicios hoteleros de la ciudad del Puyo, Provincia de Pastaza - Ureña Espinoza, Diana Carolina (2017)
The present investigation analyzes the problematic of the Hotel Maria. With the support of the information provided by the Hotel María, Ministry of Tourism among others, through the descriptive method and the quantitative and qualitative analysis of the data obtained, helped by instruments such as surveys and interviews, the necessary information was obtained to diagnose The reality of the hotel, know your services. We identified a poor promotion of hotel services and reservations and the profitability is less than expected, due to it is necessary to carry out some promotional strategies. All these suggestions of the customers and the owner, were expressed in a proposal structured on the basis of the 7 lines of action in a marketing plan landed on the reality of the Hotel, in order to allow it to implement each of the strategies In the shortest time possible and with the own resources of the establishment and with this to improve its current situation.